PENGABDIAN KEPADA MASYARAKAT TENTANG PENERAPAN ADAPTASI KEBIASAAN BARU PADA ANAK SEKOLAH MENJELANG LIBUR SEKOLAH - Ritonga, Nefonavratilova; Siregar, Nurelilasari (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
The year 2020 was an extraordinary year for Indonesia and even the whole world since the discovery of cases of pneumonia with unknown causes in Wuhan City, China. The Coronavirus Disease (COVID-19) pandemic that has occurred has caused disruption in various fields, one of which is in the fields of health and education. The first two cases of COVID-19 in Indonesia were found on March 2, 2020 in Depok, West Java. The number of COVID-19 cases in Indonesia continued to rise until at the end of March confirmed cases reached 1,414 cases. This prompted President Joko Widodo to declare a public health emergency and order the police to implement large-scale social restrictions (PSBB) in all regions in Indonesia. In order to support the sustainability of the community's economy, each region needs to urge the public to face the state of preparation for the New Habit Adaptation (IMR) according to the level of vigilance at the district/city level for the prevention and control of COVID-19. Adaptation of new habits (IMR) is very important to be socialized to the community, especially to elementary school children before school holidays, because children will definitely go on vacation and play which will cause the Covid 19 virus to move from one to another.